Irradiação e atmosfera modificada passiva na qualidade pós-colheita de goiabas 'Pedro Sato' - Campos, André José de; Fujita, Erika; Costa, Sérgio Marques [UNESP]; Neves, Leandro Camargo; Vieites, Rogério Lopes [UNESP]; Chagas, Edvan Alves (Universidade Federal de Roraima, 2011)
The aim of this study was to evaluate the effect of gamma radiation associated with modified atmosphere on postharvest quality of guavas ‘Pedro Sato’. It was used guavas from the region of Vista Alegre do Alto/São Paulo/Brazil. After harvest, the fruits were immediately transported to the Fruit and Vegetables Laboratory from the Agroindustrial Management and Technology Department, Agronomic Sciences College - UNESP - Botucatu / SP, where they were kept at 10 ° C and 90-95% RH in cold storage, for 28 days. It was used the randomized design, with factorial scheme 5 x 5, three repetitions. The first factor consisted of the following effects: control 1 (without package or irradiation), control 2 (polystyrene package/PS + package low density polyethylene/LDPE and without irradiation), treatment 1 (PS + LDPE and 0.2 kGy ), treatment 2 (PS + LDPE and 0.6 kGy) and treatment 3 (PS + LDPE and 1.0 kGy). The second factor consisted of the evaluation periods: 0, 7, 14, 21 and 28 days. The analyses were: firmness, soluble solids (SS), titratable acidity (TA), maturity index, pH, respiration rate. Concluded that high doses of irradiation promoted a negative effect on physical-chemical characteristics of guava ‘Pedro Sato’, verifying that only the lowest dose associated with modified atmosphere provided fruits with higher quality and acceptability, due to higher maturation rate and soluble solids obtained. Regarding the days of analysis, there were no positive effect of the treatments during storage, where only the early days promoted better values for the variables studied.

Objetivou-se com esse trabalho avaliar o efeito da radiação gama associada à atmosfera modificada passiva na qualidade pós-colheita de goiabas ‘Pedro Sato’. Foram utilizadas goiabas provenientes da região de Vista Alegre do Alto/SP/Brasil. Após a colheita, as goiabas foram imediatamente transportadas ao Laboratório de Frutas e Hortaliças, pertencente ao Departamento de Gestão e Tecnologia Agroindustrial, da Faculdade de Ciências Agronômicas – UNESP – Campus de Botucatu/SP, aonde foram mantidas a 10ºC e 90-95%UR em câmara frigorífica, por 28 dias. Foi utilizado o delineamento inteiramente casualizado, em esquema fatorial 5 x 5, com três repetições. O primeiro fator consistiu dos seguintes efeitos: controle 1 (sem embalagem e sem irradiação); controle 2 (embalagem de poliestireno/PS + embalagem de polietileno de baixa densidade/PEBD e sem irradiação); tratamento 1 (PS+PEBD e 0,2 kGy); tratamento 2 (PS+PEBD e 0,6 kGy) e tratamento 3 (PS+PEBD e 1,0kGy). O segundo fator consistiu dos períodos de avaliação, sendo: 0, 7, 14, 21 e 28 dias. As variáveis avaliadas, foram: firmeza, sólidos solúveis (SS), acidez titulável (AT), índice de maturação “Ratio”, pH, taxa de respiração. Concluiu-se que as altas doses de irradiação promoveram efeito negativo nas características físico-químicas da goiaba ‘Pedro Sato’, verificando que apenas a menor dose utilizada associada a atmosfera modificada proporcionou frutos com maior qualidade e aceitabilidade, devido aos maiores índice de maturação e sólidos solúveis obtidos. Em relação aos dias de análise, não foi observado efeito positivo dos tratamentos no decorrer do armazenamento, onde somente os dias iniciais promoveram os melhores valores para as variáveis estudadas.
Irradiation and passive modified atmosphere on the post-harvest quality of guavas ‘Pedro Sato’
Keywords: Cobalt 60; Conservation; Package; Psidium guajava L; Cobalto 60; Conservação; Embalagem; Psidium guajava L